PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI OPERASI HITUNG PERKALIAN DAN PEMBAGIAN DENGAN STRATEGI INDEX CARD MATCH PADA SISWA KELAS III SDN TANJUNG BATU KEC. KELUMPANG TENGAH KAB. KOTABARU - Norhayati Norhayati (STKIP Paris Barantai, 2020)
This study aims to determine whether the Index Card Match strategy can improve the mathematics learning achievement of the Multiplication and Division Counting Operations material in grade III SDN Tanjung Batu District Kelumpang Tengah Kab. Kotabaru consists of 14 students, namely 10 male students and 4 female students. Based on the results of research in cycles I, II, and III, the following data were obtained: The standard of KKM for mathematics is 70, before using Index Card Match there were only 21.4% who completed and 78.5% has not met the KKM standard. After using the Index Card Match Strategy in Mathematics lessons in the first cycle, 64.2% have completed data, and 35.7% have not completed, in the second cycle data obtained 71.4%, and 28.5% had not yet completed it, and in the third cycle data was obtained that 85.7% had completed, and 14.2% had not finished. There was an increase in student learning outcomes from pre-cycle to cycle I of 42.8%, when compared between cycle I and cycle II there was an increase of 7.1% and an increase in cycle II to cycle III was 14.2%. Keywords: Improved Learning Outcomes and Indec Card Match Strategy